Analisis Kinerja Penyaluran Produk Kredit Usaha Rakyat (KUR) Di Kabupaten Minahasa (Studi Menggunakan Metode Importance Performance Analysis (IPA) dan Potential Gain Of Costumer Value’s (PGCV)) - Masloman, Kun Fiqri Masloman Fiqri (Universitas Sam Ratulangi, 2017)
The purpose of this study to find out how the Performance of Business Credit people in PT. BRI (peresro) Tbk. Tondano Branch. know the distribution program People's Business Credit PT. Bank Rakyat Indonesia (Persero), Tbk. Tondano Branch. And how the product of People's Business Credit PT. Bank Rakyat Indonesia (Persero), Tbk. Tondano Branch. The results of this research are in the methods used are Importance Performance Analysis (IPA) and Potential Gain Customer Of Value's (PGCV)Keywords: Performance, Distribution, Product, Importance Performance Analisais (IPA), Potential Gain Customer Of Value's